Inaktivasi Bakteri Patogen Planktonik dan Biofilm oleh Sanitaiser Komersial - Ratih Dewanti Hariyadi; Cynthia CynthiaCynthia (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Cleaning and sanitizing are important aspects in providing quality and safe foods. In the US, contaminated equipment is the third most important factor contributing to foodborne disease outbreaks. The objective of this study was to evaluate the effectiveness of commercial sanitizers against planctonic cells and biofilms of pathogenic bacteria Salmonella Typhimurium and Staphylococcus aureus. Commercial sanitizers used in this study were single sanitizers (quaternary ammonium, peroxy acetic acid, coconut fatty acid) and combined sanitizers (Oxyquart®, Bioclean 520®, Bioclean 540®) at the recommended application concentrations. Of the sanitizers tested on planctonic cells, peroxy acetic acid at 100 ppm as well as Oxyquart® and Bioclean 540® at concentrations of 0.010% are effective against S. Typhimurium; while Oxyquart® at a concentration of 0.005% is the most effective sanitizer against S. aureus. The study also shows that Oxyquart® is more effective against biofilms and capable of inactivating 3.94-5.02 log CFU/cm2 of S. Typhimurium or S. aureus biofilm.